HEAVY METAL CONCENTRATION IN SOFT SEDIMENTS OF RIVER-NUN AT AMASSOMA AXIS - Alagoa, KJ, Kariye E. Lelei, Charles E.E, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The concentration levels of the heavy metals Chromium (Cr), Lead (Pb), Nickel (Ni) and Cadmium (Cd) in the sediments of River-nun at Amassoma, axis was investigated in a bid to assess how land based activities adjacent to the river affect its general health and productivity. Sediment samples were collected at different locations along the river catchment representing different land use patterns. Heavy metal characteristics were then measured using standard procedures. Result of the study show that Cr and Cd did not significantly vary (P>0.05) between sample stations. There were significant differences (P<0.05) in Ni and Pb concentrations between stations. All metal parameters were lower than the World Health Organization (WHO) suggested limit for heavy metals in fresh waters. Except Pb which was negligibly higher than the recommended limit. It can be deduced that human activities in the river catchment will not in the immediate pose a challenge on the river and its ecology